Carpal Bone Segmentation Using Fully Convolutional Neural Network - Meng, LK; Khalil, A; Nizar, MHA; Nisham, MK; Pingguan-Murphy, B; Hum, YC; Salim, MIM; Lai, KW (Bentham Science Publisher, 2024)
Indexed by Scopus